The last battle soldier settlement in Australia, 1916-1939 - Scates, Bruce 1957-; Oppenheimer, Melanie 1957- (Cambridge University Press, 2016)
When Australian soldiers returned from the First World War they were offered the chance to settle on 'land fit for heroes'. Promotional material painted a picture of prosperous farms and contented families, appealing to returned servicepeople and their families hoping for a fresh start. Yet just 20 years after the inception of these soldier settlement schemes, fewer than half of the settlers remained on their properties. In this timely book, based on recently uncovered archives, Bruce Scates and Melanie Oppenheimer map out a deeply personal history of the soldiers' struggle to transition from Anzac to farmer and provider. At its foundation lie thousands of individual life stories shaped by imperfect repatriation policies. The Last Battle examines the environmental challenges, the difficulties presented by the physical and psychological damage many soldiers had sustained during the war, and the vital roles of women and children